Scientific American. – 1866. – Vol. 15, № 5 - б/а (New York. Munn & Company, 1866)
A weekly journal of practical information, art, science, mechanics, chemistry and manufactures.
Scientific American. Vol. 15, № 1–26. – New York, 1866. – P. 1–440.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of medicine; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Agricultural history; Research Subject Categories::NATURAL SCIENCES::Physics; Research Subject Categories::NATURAL SCIENCES::Chemistry; July 28, 1866; Recent American Patents; Patents; Improved Brick Machine; Wolliston’s Brick Machine; On Flying Machines; Spaulding’s Patent Broom Head; Parsons’s Car Coupling; Jacobs’s Piston Packing; Holt & Thompson’s Improved Oiler